The Effectiveness of Policy Implementation in Managing State-Owned Property: Case Study of Ministry of State Secretariat - Eko Sugiyanto; Abdul Gani Hamumuroata (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effectiveness of the implementation of the State Property management policy at the Ministry of State Secretariat in 2019 using the George Edwards III policy implementation model. This qualitative research shows that the utilization of state assets managed by the Public Service Agency for the Center for Regional Management (BLU PPK) Gelora Bung Karno and Kemayoran has been effective from the communication that the leadership at BLU PPK actively coordinates in strategic policies. The development of the cooperation division has been effective in encouraging mutually beneficial cooperation with the private sector. The attitude of the implementers has been effective in increasing non-tax state revenue. The bureaucratic structure is still weak due to ineffective aspects of supervision and internal control of commercial cooperation agreements that do not meet the criteria for the 2017 Minister of Finance regulation. The four dimensions must be strengthened by the dimensions of internal supervision and control in order to achieve success in policy implementation.